Energy Consumption and Economic Growth: Evidence from Low-Income Countries in Sub-Saharan Africa - DOGAN, Eyup (International Journal of Energy Economics and Policy, 2014)
The main purpose of this paper is to investigate the causality relationship between energy consumption and economic growth in four low-income countries in Sub-Saharan Africa using the econometrics in time-series methods. Along the estimation process, I use the annual data on energy consumption and real GDP per capita over the years of 1971 and 2011. The results of the ADF unit root test show that the time series are not stationary for all countries at levels, but log of economic growth in Benin and Congo become stationary after taking the differences of the data, and log of energy consumption become stationary for all countries and LGR in Kenya and Zimbabwe are found to be stationary after taking the second differences of the time-series. The findings of the Johansen co-integration test demonstrate that the variables LEC and LGR are not co-integrated for the cases of Kenya and Zimbabwe, so no long-run relationship between the variables arises in any country. The Granger causality test indicates that there is a unidirectional causality running from energy use to economic growth in Kenya and no causality linkage between EC and GR in Benin, Congo and Zimbabwe. Keywords: economic growth; energy consumption; causality test JEL Classifications: C22; O43